Gaya Komunikasi Sutradara dalam Mengarahkan Pemain dalam Film Turah - Arman, Joni; Aunul, Sofia; Gusmanti, Reza; Karisma, Ika (Universitas Mercu Buana, 2024)
The director's communication style is an important element in the process of directing players according to the script and storyline of a film. This paper aims to describe the director's communication style in the pre-production and production stages. This paper uses a descriptive qualitative approach with data collection techniques by interviewing the director and Turah's cast. The results of the study found that the director of the Turah film, Wicaksono Wisnu Legowo, used a communication style that dynamic which means that at each stage of film production, the director uses a different style. In the pre-production stage the director uses a reciprocal communication style in the preparatory sessions with the actors and a freelance communication style in the rehearsal sessions while in the production stage of the mise en scene sessions and directing the actors, the director uses a structured communication style and a dynamic communication style in the pre-take preparation sessions.